Islandsk sprog og dansk tunge: Islandsk sprog og litteraturs betydning for nationsopbygningen i Danmark - Hauksdóttir, Auður (Danske Studier, 2020)
The Icelandic language and medieval literature played an important role in the development of Danish national identity. Icelandic manuscripts served as a key source for the writing of Denmark’s earliest history and attracted widespread interest among Danish scholars. Growing nationalist sentiment was increasingly directed at the mother tongue, which was considered a major cornerstone of national identity. Knowledge of Icelandic could be of key importance for researching the Danish language, and for interpreting the meaning of older writings. Languages that had a long tradition of writing and prestigious literature were highly respected, and it was significant to find an unbroken connection between the contemporary and original language. In this respect, the Icelandic language had characteristics that Danish no longer had. Interest of Danes in Icelandic language and literature, together with the important role they were accorded in the age of Romanticism, meant a great deal to Icelanders. Apart from creating job opportunities and income in Copenhagen, these conditions fuelled their pride as Icelanders and boosted awareness of the significance of language for Icelandic nationality and culture. As a result, interest on the part of Danes in Icelandic language and culture contributed to the growth and development of both Icelandic and Danish.